Mandibular actinomyces osteomyelitis - Bistra Blagova; Lina Malinova; Vesela Ivanova (Wolters Kluwer Medknow Publications, 2022)
Actinomycosis caused by the Actinomyces genus can affect both soft and bone tissues. Its diagnosis depends on positive culture or identification of Actinomyces colonies and sulfur granules in histological specimens. This article aims to report a clinical case of actinomycosis in the mandible. The diagnosis of actinomycosis osteomyelitis was confirmed by bone biopsy in a female with a long-standing history of generalized periodontal disease. She underwent debridement of necrotic tissue in the region, and the material was sent for histopathological analysis, which revealed chronic localized actinomycosis osteomyelitis. The patient responded well to prompt systemic antibiotics and local surgical measures with complete resolution of the infection. Clinicians should be aware of the possibility of actinomycosis arising in generalized periodontal disease and the importance of bone biopsies and cultures in arriving at a definitive and timely diagnosis. The accurate diagnosis of actinomycosis is crucial for the successful treatment outcome.